Membentuk Karakter Religius Sosial Anak Jalanan di Kota Parepare: Membentuk Karakter Religius Sosial Anak Jalanan di Kota Parepare - Silmi Qurota Ayun Ariadin; Andi Muhammad Ikbal Salam (IAIN Parepare, 2025)
Siguru community, founded in the city of Parepare, focuses on the issue of street children, especially those who do not receive formal education, either at home or at school. Education is essential to help children grow and develop, as well as to shape their character, which they will use in their social lives. This study uses a qualitative approach with data collection techniques such as observation, interviews, and documentation. The primary data for this study are the founders and volunteers who teach. To analyze the data themselves. The community is a social community that focuses on assisting street children, especially those who do not receive formal education either at home or at school. Education is a fundamental aspect in helping children grow and develop, as well as forming the character that is essential in their social lives. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Data analysis is carried out through a process of reduction, presentation, and conclusion drawing with reference to role theory and social construction theory. The results show that the Siguru Community plays an important role as a substitute for the role of family and educators for street children. This community provides non-formal education through teaching reading, writing, arithmetic, and religious learning as the foundation for religious character building. Through a value-based approach, Siguru volunteers encourage children to learn the basic teachings of Islam, such as reading the Quran, daily prayers, and religious practices such as salat and wudu. In addition, this community strives to build motivation and enthusiasm for learning among street children so that they have goals and hopes for the future. Religious character building is instilled through role modeling, practicing polite behavior, and strengthening moral values in daily activities.